Perception of Undergraduates on the Utilization of Quizalize App for Formative Assessment in Online Educational Programme in the University of Ilorin - Temitayo O. Onasanya; Bridget I. Otemuyiwa; Samuel A. Onasanya (West African Journal of Open and Flexible Learning, 2020)
This paper investigated the perception of undergraduates on the utilization of Quizalize app for formative assessment in online educational programme in the University of Ilorin. The study adopted a descriptive survey research design to evaluate the ease of use, eﬃciency, eﬃcacy and challenges of using quizalize application for formative assessment in an online education. The sample for the study comprised of one hundred and ﬁfty, 400 level students (2018/19 academic session) of educational technology department, University of Ilorin. Four research questions and four research hypotheses piloted the course of the research. The only instrument used for data collection was adapted from Bicen & Kocakoyun (2018) and Elmahdi, Al-Hattami & Fawzi (2018), and titled: “Utilization of Quizalize application for Formative Assessment Questionnaire (UQFAQ)”. A reliability coeﬃcient of 0.76 was obtained using Cronbach's Alpha. The instrument was administered electronically and a 100% return rate was achieved. Data collected was analysed using a set mean value of 2.50 as “agreed”, while t-test was employed for analysis on the hypotheses using IBM SPSS statistics 20. Findings revealed among others that quizalize were easy to use, eﬃcient and there were no signiﬁcant diﬀerences between the perception of the male and female students. Based on the ﬁndings, it was recommended that quizalize application be integrated into the online educational programme and that online lecturers should engage the use of quizalize application for formative assessment so as to the provide students and the lecturers with continuous, real time information.